Two subsets of stem-like CD8+ memory T cell progenitors with distinct fate commitments in humans - Galletti, Giovanni; De Simone, Gabriele; Mazza, Emilia M. C.; Puccio, Simone; Mezzanotte, Claudia; Bi, Timothy M.; Davydov, Alexey N.; Metsger, Maria; Scamardella, Eloise; Alvisi, Giorgia; De Paoli, Federica; Zanon, Veronica; et al. (Nature Immunology, 2020)
T cell memory relies on the generation of antigen-specific progenitors with stem-like properties. However, the identity of these progenitors has remained unclear, precluding a full understanding of the differentiation trajectories that underpin the heterogeneity of antigen-experienced T cells. We used a systematic approach guided by single-cell RNA-sequencing data to map the organizational structure of the human CD8+ memory T cell pool under physiological conditions. We identified two previously unrecognized subsets of clonally, epigenetically, functionally, phenotypically and transcriptionally distinct stem-like CD8+ memory T cells. Progenitors lacking the inhibitory receptors programmed death-1 (PD-1) and T cell immunoreceptor with Ig and ITIM domains (TIGIT) were committed to a functional lineage, whereas progenitors expressing PD-1 and TIGIT were committed to a dysfunctional, exhausted-like lineage. Collectively, these data reveal the existence of parallel differentiation programs in the human CD8+ memory T cell pool, with potentially broad implications for the development of immunotherapies and vaccines.
CRIS-Team Scopus Importer:2023-03-23